In Situ Polymerized Hollow Mesoporous Organosilica Biocatalysis Nanoreactor for Enhancing ROS‐Mediated Anticancer Therapy. (4th November 2019) - Li, Ling; Yang, Zhen; Fan, Wenpei; He, Liangcan; Cui, Cao; Zou, Jianhua; Tang, Wei; Jacobson, Orit; Wang, Zhantong; Niu, Gang; Hu, Shuo; Chen, Xiaoyuan
Abstract: The combination of reactive oxygen species (ROS)‐involved photodynamic therapy (PDT) and chemodynamic therapy (CDT) holds great promise for enhancing ROS‐mediated cancer treatment. Herein, an in situ polymerized hollow mesoporous organosilica nanoparticle (HMON) biocatalysis nanoreactor is reported to integrate the synergistic effect of PDT/CDT for enhancing ROS‐mediated pancreatic ductal adenocarcinoma treatment. 2‐(1‐hexyloxyethyl)‐2‐devinylpyropheophorbide‐a photosensitizer is hybridized within the framework of HMON via an "in situ framework growth" approach. Then, the hollow cavity of HMONs is exploited as a nanoreactor for "in situ polymerization" to synthesize the polymer containing thiol groups, thereby enabling the immobilization of ultrasmall gold nanoparticles, which behave like glucose oxidase‐like nanozyme, converting glucose into H2 O2 to provide self‐supplied H2 O2 for CDT. Meanwhile, Cu 2+ ‐tannic acid complexes are further deposited on the surface of HMONs (HMON‐Au@Cu‐TA) to initiate Fenton‐like reaction to covert the self‐supplied H2 O2 into OH, a highly toxic ROS. Finally, collagenase (Col), which can degrade the collagen I fiber in the extracellular matrix, is loaded into HMON‐Au@Cu‐TA to enhance the penetration of HMONs and O2 infiltration for enhanced PDT. This study provides a good paradigm for enhancing ROS‐mediated antitumor efficacy. Meanwhile, this research offers a new method to broaden the application of silica based nanotheranostics. Abstract : An in situ polymerized hollow mesoporous organosilica biocatalysis nanoreactor is constructed to integrate the synergistic effect of photodynamic/chemodynamic therapy for enhancing reactive oxygen species‐mediated pancreatic ductal adenocarcinoma treatment.